A systematic review of the evidence supporting post-operative diuretic use following cardiopulmonary bypass in children with Congenital Heart Disease. (4th May 2021) - Foote, Henry P.; Hornik, Christoph P.; Hill, Kevin D.; Rotta, Alexandre T.; Chamberlain, Reid; Thompson, Elizabeth J.
Abstract: Background: Paediatric cardiac surgery on cardiopulmonary bypass induces substantial physiologic changes that contribute to post-operative morbidity and mortality. Fluid overload and oedema are prevalent complications, routinely treated with diuretics. The optimal diuretic choice, timing of initiation, dose, and interval remain largely unknown. Methods: To guide clinical practice and future studies, we used PubMed and EMBASE to systematically review the existing literature of clinical trials involving diuretics following cardiac surgery from 2000 to 2020 in children aged 0–18 years. Studies were assessed by two reviewers to ensure that they met eligibility criteria. Results: We identified nine studies of 430 children across four medication classes. Five studies were retrospective, and four were prospective, two of which included randomisation. All were single centre. There were five primary endpoints – urine output, acute kidney injury, fluid balance, change in serum bicarbonate level, and required dose of diuretic. Included studies showed early post-operative diuretic resistance, suggesting higher initial doses. Two studies of ethacrynic acid showed increased urine output and lower diuretic requirement compared to furosemide. Children receiving peritoneal dialysis were less likely to develop fluid overload than those receiving furosemide. Chlorothiazide, acetazolamide, and tolvaptan demonstrated potential benefit as adjuncts to traditional diuretic regimens. Conclusions: Early diuretic resistance is seen in children following cardiopulmonary bypass. Ethacrynic acid appears superior to furosemide. Adjunct diuretic therapies may provide additional benefit. Study populations were heterogeneous and endpoints varied. Standardised, validated endpoints and pragmatic trial designs may allow investigators to determine the optimal diuretic, timing of initiation, dose, and interval to improve post-operative outcomes.